SWOT mission enables high-precision and wide-coverage lake water levels monitoring on the Tibetan Plateau - Suhui Wu; Yu Cai; Chang-Qing Ke; Yao Xiao; Haili Li; Zhiyue He; Zheng Duan (Journal of Hydrology: Regional Studies)
Study region: The Tibetan Plateau (TP) is a high-altitude region characterized by harsh environmental conditions and limited accessibility, making the monitoring of its numerous lakes a significant challenge. This region is crucial for hydrological studies, and its numerous lakes play an important role in regional water dynamics and climate change research. Study focus: This study evaluates the applicability and accuracy of Surface Water and Ocean Topography (SWOT) satellite data in monitoring lake water levels across the TP. The study compares SWOT-derived lake levels with data from the Ice, Cloud, and Land Elevation Satellite-2 (ICESat-2), instead of relying on in situ measurements. New hydrological insights for the region: Based on SWOT data, lake water levels for 1919 lakes were successfully extracted, covering approximately 99 % of lakes larger than 0.2 km² and filling observation gaps in around 800 lakes compared to traditional altimetry satellites. Validation against ICESat-2 data demonstrated high consistency, with an average bias of −0.01 ± 0.13 m and a mean absolute error (MAE) of less than 0.1 m. SWOT outperformed other radar altimeters in monitoring lake levels when compared to ICESat-2. Furthermore, by integrating SWOT data with other altimetry-derived lake level products, we created high-frequency time series data for 12 lakes, which showed strong correlations with the DAHITI and Hydroweb datasets. These results highlight SWOT's potential for global lake monitoring, offering new opportunities for water resource management and climate change research.